Hematological and Serological diagnosis of Enzootic Bovine Leukosis - ΔΗΜΗΤΡΙΑΔΗΣ, I.; ΣΕΪΤΑΡΙΔΗΣ, K.; ΠΑΠΑΔΟΠΟΥΛΟΣ, Ε. (Journal of the Hellenic Veterinary Medical Society, 2019)
45 cows of two heards with serological evidence of the disease were examined by using the serological and hematological testings at the same time. In a previous survey only there two herds had shown serological evidence of enzootic bovine leukosis. From these 45 animals 6 were found positive after hematological testing and 5 after serological testing. 3 cows negative after serological testing were found positive after the hematological testings (37,5%), 2 cows negative after the hematological testing were found positive after the serological testing (25%) and the other 3 cows were positive to both the serological and hematological testings (37,5%). The specific reagents for the immunodiffusion test that is agar, antigen and hyperimmune antisera were kindly supplied by Behringwerke A.E. Germany and we take the opportunity to express our warmest thanks for this Firm.